Applying Benford's Law to individual financial reports: An empirical investigation on the basis of SEC XBRL filings - Henselmann, Klaus; Scherr, Elisabeth; Ditter, Dominik (2012)
This study examines whether investors could use Benford’s Law as an aid in determining high-risk areas for investing within their process of decision-making. The business reporting standard XBRL offers the opportunity to easily extract and analyze a sufficient number of monetary items out of single annual reports for statistical analysis purposes. Using SEC XBRL filings of S&P 500 companies (Fiscal Year 2010), we derive first digit distributions for single companies and measure the deviation from the Benford distribution. On average, we find that for all monetary numbers that are contained in the examined XBRL reports, the first digit distribution follows Benford’s Law. A firm and industry-specific analysis reveals the industry Financials as being most conspicuous. Taken together, the empirical results suggest that the application of Benford’s Law to annual reports might be a useful analytical tool for investor
WiSo-Import:2015-08-12:3367
Keywords: Benford’sches Gesetz; XBRL; Interactive Data; SEC Veröffentlichungen; Bilanzanalyse; Bilanzfälschung

Besser spät als nie? Eine Untersuchung des ,Reporting Lag' der unterjährigen Regelpublizität am deutschen Kapitalmarkt - Henselmann, Klaus; Scherr, Elisabeth; Ditter, Dominik; Hummelt, Katharina (Betriebswirtschaftliche Forschung und Praxis, 2017)

Directors' Dealings am deutschen Kapitalmarkt - Büchs, Daniel; Ditter, Dominik; Henselmann, Klaus; Hering, Jörg; Götz, Michael (Zeitschrift für Corporate Governance, 2016)

Irregularities in Accounting Numbers and Earnings Management: A Novel Approach Based on SEC XBRL Filings - Henselmann, Klaus; Ditter, Dominik; Scherr, Elisabeth (Journal of Emerging Technologies in Accounting, 2015)

Too little, too late? Ein empirisch gestützter Beitrag zur Bilanzierung der Kreditrisikovorsorge - Henselmann, Klaus; Ditter, Dominik; Holstein, Thomas (Internationale und kapitalmarktorientierte Rechnungslegung, 2014)

Using XBRL Technology to Extract Competitive Information from Financial Statements - Ditter, Dominik; Henselmann, Klaus; Scherr, Elisabeth (Journal of Intelligence Studies in Business, 2011)